Sinonasal Melioidosis in a Returned Traveller Presenting with Nasal Cellulitis and Sinusitis - Rebecca Sin Mei Lim; Sam Flatman; Markus C. Dahm (Case Reports in Otolaryngology)
We illustrate a case involving a 51-year-old man who presented to a tertiary hospital with sepsis secondary to an abscess of the nasal vestibule and pustular eruptions of the nasal mucosa. Associated cellulitis extended across the face to the eye, and mucosal thickening of the sinuses was seen on computed tomography. The patient underwent incision and drainage and endoscopic sinus surgery. Blood cultures and swabs were positive for a gram-negative bacillus, Burkholderia pseudomallei. He had multiple risk factors including travel to an endemic area. The patient received extended antibiotic therapy in keeping with published national guidelines. Melioidosis is caused by Burkholderia pseudomallei, found in the soil in Northern Australia and Asia. It is transmitted via cutaneous or inhaled routes, leading to pneumonia, skin or soft tissue abscesses, and genitourinary infections. Risk factors include diabetes, chronic lung disease, and alcohol abuse. It can exist as a latent, active, or reactivated infection. A high mortality rate has been identified in patients with sepsis. Melioidosis is endemic in tropical Northern Australia and northeastern Thailand where it is the most common cause of severe community-acquired sepsis. There is one other report of melioidosis in the literature involving orbital cellulitis and sinusitis.